Indonesian Throughflow promoted eastward propagation of the Madden-Julian Oscillation - Libin Ma; Mingting Li; Fei Liu; Juan Li (npj Climate and Atmospheric Science, 2024)
Abstract Understanding the impacts of the Indonesian Throughflow (ITF) on the eastward propagation of the Madden-Julian Oscillation (MJO) is crucial for accurately simulating the MJO and achieving high-skill sub-seasonal predictions. Our analyses demonstrate a significant enhancement of MJO eastward propagation due to the strong ITF. Blocking the ITF decreases the eastward sea surface temperature (SST) gradient over the tropical Indian Ocean, hindering MJO propagation across the Maritime Continent (MC). Removing the MJO circulation-induced intraseasonal variability of the ITF transport also weakens the eastward propagation of the MJO, as the MJO easterly winds enhance the ITF transport and warm the eastern tropical Indian Ocean. These experiments reveal that mean and intraseasonal variability of the ITF transport contribute to 73% and 42% of the eastward propagation of the MJO over the MC, respectively. The findings presented in this study highlight the significant role of the ITF in shaping the propagation of the MJO.